COMPARISON OF CHEMICAL AND ELECTROCHEMICAL TREATMENT PROCESSES FOR WOOL YARN DYEING EFFLUENTS - Ulucan Altuntas, Kubra; Ilhan, Fatih; Dogan, Can; Kurt, Ugur (YILDIZ TECHNICAL UNIV, 2020)
Textile industry is one of the sectors that consume plenty of water and this situation increases the threat of contamination on the receiving water environments. In this study, treatment method performances of chemical coagulation, electrocoagulation, Fenton and electrofenton for wool yarn dyeing effluents were investigated by considering COD and TOC parameters and; advantages and disadvantages of each process were evaluated. Response surface methodology (RSM) was applied to optimize Fenton process and, in order to achieve COD and TOC removed by 90.5% 77.4%, respectively, 143 minutes of reaction time was found to be required. Optimum pH for Fenton process was determined via RSM as 3.28 pH. The required Fe dosage and H2O2 dosage was found to be 1135 mg/L and 1822 mg/L, respectively. When Fenton, electrofenton, coagulation and electrocoagulation processes were compared in terms of COD removal, the most effective process is found to be Fenton process and 88%, 77%, 30% and 42% of COD removals were observed, respectively. When the amount of sludge formed per treated COD is compared, it was observed that the least sludge was obtained via electrofenton process in term kg sludge/kg COD, where the maximum sludge was obtained in chemical coagulation process with 73% higher than electrofenton.
Keywords: Textile wastewater; advance oxidation processes; chemical coagulation; electrocoagulation; electrofenton; fenton; TEXTILE WASTE-WATER; PROCESS OPTIMIZATION; FENTON PROCESS; COAGULATION; PRETREATMENT; OXIDATION; Engineering